'Never grow old, never die': Vampires, narcissism and simulacra. Issue 1 (30th October 2012) - Godwin, Victoria L.
This article builds upon examinations of vampires' metaphoric threat to individuality as part of its larger argument concerning vampires' mainstream popularity. Tensions between narcissism and simulacra illuminate how vampires express intersecting cultural concerns over mechanical, cultural and biological reproduction. First, vampires reflect cultural anxieties over monoculture and loss of individuality by reducing individuals to a means to transmit information: like media images, or Jean Baudrillard's clones. Rather than marking yet another victim as Other, vampires actually subjugate yet another individual to monoculture, converting yet another body into a medium for cultural reproduction and the reproduction of desire. Second, reproduced images' false permanence undermines narcissistic fantasies of eternal vampire life. Third, people and love become commodities enhancing self-image but not self-development. Finally, whereas vampirism arrests physical ageing, the Peter Pan syndrome arrests emotional maturation. Children never grow up, and their continued dependence never reminds parents of ageing, death and replacement by new generations.